Financial imperatives and constraints towards funding the SADC standby force - Ndaguba, E.A.; Nzewi, O.I. and Shai, K.B. (2018)
Achievable and viable peace and security efforts in Southern Africa Development Community (SADC) have been limited by an over dependence on foreign and international peacekeeping. The aim of this article is to unpack financial imperatives and constraints towards funding the SADC standby force (SADCSF). Through this the article hopes to provide lessons towards a suitable and sustainable funding mechanism aimed at addressing the financial challenges confronting African standby forces in peace operations. In particular, this article focuses on the SADCSF since its establishment in 2007. This article uses information from existing statistical and research data to first, identify existing funding models in international (regional and continental) peace operation and stand-by forces across the globe. Second, using four critical analytical frames (financial viability, the nature of regionalism, fiscal sustainability and economic landscape), the article highlights various implications of a lack of funding mechanism for regional peace and security in Africa. Third, the article shows that the following are critical to find a sustainable funding mechanism for the SADCSF: the financially demanding variable geometric nature of regional integration in Africa; the proliferation of security agencies; the complex nature of terrorism and interventions; the cost of skill acquisition and training of the multidisciplinary personnel; payment of wounded soldiers and contingents and member state tight budget. Based on international experiences and local realities expounded, this article suggests lessons towards building a suitable and sustainable funding mechanism for African peace and security in general, and regional standby forces in particular. - Reproduced.
Keywords: Africa's regional governance; Regionalism; SADCSF; United Nations